Borderlands in European gender studies : beyond the East-West frontier - Kulawik, Teresa; Kravchenko, Zhanna (New York : Routledge, 2019)
"Challenging persistent geopolitical asymmetries in feminist knowledge production, this collection depicts collisions between concepts and lived experiences, between academic feminism and political activism, between the West as generalizable and the East as the concrete Other. Borderlands narrows the gap between cultural analysis and social theory, addressing feminist theory's epistemological foundations and its capacity to confront the legacies of colonialism and socialism. The contributions demonstrate the enduring worth of feminist concepts for critical analysis, conceptualize resistance to multiple forms of oppression, and identify the implications of the decoupling of cultural and social feminist critique for the analysis of gender relations in a post-socialist space. This book will be of import to activists and researchers in women's and gender studies, comparative gender politics and policy, political science, sociology, contemporary history, and European studies. It is suitable for use as a supplemental text for advanced undergraduate and graduate courses in a range of fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Feminism -- Europe, Eastern -- History; Feminism -- Europe, Western -- History; Sex role -- Europe, Eastern -- History; Sex role -- Europe, Western -- History; SOCIAL SCIENCE / Sociology / General